The use of alamang (Acetes Indicus) in kroepeck - Antiola, Gracia L. (1976)
The primary aim of the study was to formulate a standardized procedure for making kroepeck that would provide a maximum source of protein with a minimum quantity of carbohydrate. The study was divided into 4 phases. The first phase involved the determination of optimum combination of rice and alamang. The second phase involved the determination of the effect of different ratios of water to rice. The third phase involved the determination of moisture content of the dried kroepeck that would give a desired puff and crisp fried product. The fourth phase involved the determination of salt concentration that would enhance the characteristic alamang flavor.Subjective tests were done at each phase to evaluate color, flavor, shape, texture and general acceptability. Objective tests were done on both the dried and the fried products. Dry milled rice was mixed with alamang, water, salt, MSG, and lime solution in a Warning Blendor to reduce particle size in the dispersion. This dispersion was poured onto trays and steamed to form thin translucent sheets which were dried to 8% moisture, then fried. From the study, a product was developed which had 80% alamang, 20% rice, 120% water, based on the weight of rice, and 0.127% salt, based on the weight of alamang. Specifically for the basic recipe, these are 23.33 g fresh alamang, 30.12 g rice, 36.14 g water, and 0.5 g salt. The fried kroepeck was crisp, yellow, curled, whole with small blisters on the surface. It had a distinct alamang flavor and was pleasingly salty. Its mean score of 6.9 by a panel of judges was equivalent to like moderately.